AUDIT OPERASIONAL PADA SIKLUS PENDAPATAN INTERNET SERVICE PROVIDER X DI SURABAYA - Febriyani Santoso; Stevanus Hadi Darmadji (CALYPTRA, 2018)
Abstract - This study was conducted on one of the ISPs in Surabaya. The author uses operational audits to evaluate and improve the effectiveness, efficiency, and economy of the revenue cycle, particularly sales activities, receivables management, and billing. Data collection method in this research is by interview, observation, and document analysis. From this research note that the activity of sale, management of receivable, and billing at X company still not effective, efficient, and economy. This happens because the company is less assertive in applying the rules that have been made. Thus, the authors recommend to be more assertive in the application of regulations that have been made. In additions, the author also recommends to change some existing rules. This recommendation is given to the company to survive the changes and competitors that exist.